Inflammation as a central mechanism: interactions among epithelial, immune, and neural units in dry eye disease and their therapeutic implications - Han Yu; Xinru Wang; Suxia Li (Journal of Translational Medicine, 2026)
Abstract Dry eye disease (DED) is a prevalent multifactorial ocular surface disorder. Early research primarily attributed its pathogenesis to insufficient tear secretion or excessive tear evaporation. Advances in mechanistic research have shifted the academic understanding from a narrow tear film-centric perspective toward an integrated framework of disrupted overall ocular surface homeostasis. Cumulative evidence has validated inflammation as the core mechanism driving DED onset and its persistent, refractory progression. Corneal epithelial injury acts as the initiating event of pathological lesions; barrier breakdown triggers the release of damage-associated molecular patterns that activate innate immune cells to secrete abundant proinflammatory mediators and further impair epithelial architecture and goblet cell function. As one of the central regulators governing the entire pathological cascade, corneal nerves undergo morphological and functional remodeling under chronic inflammatory and hyperosmotic stimuli, presenting reduced nerve fiber density and hyperalgesia, and continuous secretion of neuropeptides to induce neurogenic inflammation, while neural dysfunction also suppresses tear secretion and hinders epithelial repair to persistently amplify immune dysregulation and tissue injury. A sophisticated interactive circuit is thereby formed among epithelial, immune and neural compartments, and analyses confined to a single compartment cannot fully explain the diverse symptoms and chronic progression of dry eye disease, yet systematic collation of their interconnected mechanisms remains absent in current reviews. Accordingly, this paper constructs an integrated epithelial–immune–neural unit model to systematically elaborate bidirectional crosstalk among the three ocular surface compartments: disrupted epithelial barrier releases inflammatory cytokines to trigger excessive immune activation and corneal neural damage; injured nerves secrete neuropeptides to further amplify immune responses; sustained aberrant immune and neural signaling jointly inhibit epithelial repair and regeneration, and the reciprocal bidirectional regulation of the three compartments ultimately establishes a self-amplifying pathological vicious cycle. Complete pathological circuit of inflammation-mediated dynamic crosstalk among the ocular surface epithelial, immune and nervous systems, and deeply dissects the core molecular mechanisms underlying the chronicity of dry eye disease. On this basis, we summarize the inherent limitations of existing anti-inflammatory therapeutic strategies and clarify the fundamental reason why single symptomatic intervention fails to block the vicious cycle of the tripartite system. Furthermore, we propose that future clinical diagnosis and treatment should shift from the conventional broad-spectrum anti-inflammatory paradigm to precise regulation targeting the multidimensional pathological interactive network, providing theoretical foundations and research support for improving the mechanistic system of dry eye disease and developing novel targeted intervention strategies.